Relationship Of Vegetable And Fruit Consumption With Central Obesity In Adult In Pasar Ikan Community Health Centers Bengkulu City In 2018 - Ketut Murni; Desri Suryani; Tetes Wahyu W (Politeknik Kesehatan Kemenkes Jakarta II, 2019)
Adulthood was where the nutritional needs of the adult age changed according to the age group. Lifestyle changes, in accordance with the changes in diet from traditional food to modern food habits led to overweight and obesity. The purpose of this study was to determine the relationship of vegetable and fruit consumption with the incidence of central obesity in adults in Pasar Ikan Bengkulu Health Center of Bengkulu City in 2018. This research was descriptive research with cross-sectional approach. The location of this research was in Pasar Ikan Bengkulu Health Center of Bengkulu City. The technique of getting samplis was by using simple random sampling with the sample of 74 sampel. The data was colledted by using interview and FFQ semi kuantitatif, which then analyzed by univariate and bivariate. The results of this research were 82,4% for vegetable consumption which was included in poor category, 55.4% fruit consumption which was included in good category and 78.4% for waist circumference which was included in central obesity, it was tested by using chi square test. The result showed that there was no relationship between the habits of consuming vegetables with the incidence of central obesity (ρ> 0.05) and there was no association between the habits of consuming fruit with the incidence of central obesity (ρ> 0.05). It was important to provide counseling about the importance of eating fruits and vegetables so the obese can always control their weight and add insight to constantly adjust their diet.